2022
DOI: 10.1093/cdn/nzac095
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Ferritin Concentrationsamong Patients Consuming a Dark-Green Leafy Vegetable–Rich, Low Inflammatory Foods Everyday (LIFE) Diet

Abstract: Background Ferritin is an iron containing protein and acute phase reactant, which may be elevated due to systemic iron overload or inflammation. Various diseases are associated with excess iron, but therapeutic iron chelation is suboptimal. Prior studies suggest that several plant phytochemicals possess iron chelating properties, indicating that a plant-based diet may benefit patients with iron overload. Objectives To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Plant-based foods (non-heme iron source) are rich in fiber, phytate, oxalate, and/or polyphenols which could chelate with iron as an inhibitor of iron bioavailability, and they have less iron absorption compared with heme iron food sources [47][48][49]; thus, the plant-based DP (DP-1) could be correlated with a reduction in serum ferritin levels. Our study demonstrated that DP-1 was correlated with reduced odds of low serum folate and vitamin D levels in pregnant women.…”
Section: Association Of Dps With Serum-anemia-related Biomarkersmentioning
confidence: 99%
“…Plant-based foods (non-heme iron source) are rich in fiber, phytate, oxalate, and/or polyphenols which could chelate with iron as an inhibitor of iron bioavailability, and they have less iron absorption compared with heme iron food sources [47][48][49]; thus, the plant-based DP (DP-1) could be correlated with a reduction in serum ferritin levels. Our study demonstrated that DP-1 was correlated with reduced odds of low serum folate and vitamin D levels in pregnant women.…”
Section: Association Of Dps With Serum-anemia-related Biomarkersmentioning
confidence: 99%